Therapeutic Effectiveness of an Antiseptic Drug for Ulcerative Finger Lesions in Artiodactyls - Leshchenko, Tatyana; Mikhailova, Irina; Yevglevsky , Alexey; Finageev, Evgeniy; Finageeva, Maya; Mikhailova, Olesya (KnE Life Sciences, 2021)
The most common surgical pathology of cattle and small ruminants is purulo-necrotic disease in the hoof, which is caused by deep neurotic-dystrophic disorders and is the result of exposure to exogenous and endogenous factors, as well as inadequate, monotonous feeding and non-compliance with hygienic and quarantine measures. The success of the control of purulent-necrotic processes in the area of the hoof depends on the timely detection of sick animals, their correct treatment and effective preventative work. Scientists have proposed many approaches and methods for treating animals that have hoof diseases, but there is no consensus about the effectiveness of the existing drugs. For the treatment of cattle and small ruminants with purulo-necrotic disease of the hoof, we proposed a new antiseptic drug with bacteriostatic, fungicidal, astringent and regenerating effects. This drug contains copper sulfate, boric acid and succinic acid. It is applied as a powder. The healing of the purulo-necrotic ulcers in the experimental animals occurred under a fibrin-tissue scab, and by the 10th day, the abnormal focus was filled with granulations followed by epithelization, which was explained by the energetic metabolic effect on the cells of the succinic acid included in the drug. The advantage of the proposed method of treatment is in the simplicity of the technical preparation of the powder under the conditions of production and in the rapid recovery of animals. The powder does not possess inhibitory properties and does not have a toxic effect. Keywords: cows, sheep, ulcers, treatment, new powder